Implementing Merdeka Curriculum to Improve Teacher Professional Services in Elementary Schools - Rafi Taris Mafazi (Borong Newinera Publisher, 2023)
The background of this research is to examine how the implementation of an independent curriculum can improve the professional services of teachers in elementary schools. This research aims to describe and examine the urgency of implementing the independent curriculum for professional teacher services in elementary schools. The method in this research is included in the type of qualitative research with the research method used is literature study with the data sources used are various literature such as journals and relevant books. The results of this research are that from the existence of an independent curriculum starting from the way teachers collaborate learning with technology and differentiated learning into the existing educational process, this will have a good impact, especially on teacher professionalism and how the teaching process is carried out by teachers to students. in schools by using an independent curriculum in the educational process so that this will have the impact that educational orientation is not only oriented towards competency but also how the independent curriculum will have an influence in increasing the professionalism of teachers themselves.